High temperature treatment on the eggs of the mosquito, Culex quinquefasciatus Say and its effects on the subsequent stages developed therefrom (Journal of the Asiatic Society of Bangladesh, Science, 2014)
The eggs of Culex quinquefasciatus Say (Diptera: Culicidae) were exposed to 40oC for different exposure periods (viz. half an hour, one, two and four hours) and control (room temperature, 28±6oC); the percentage of egg hatching ranged from 74.14 to 96.33 (F=215.593, P